2020
DOI: 10.1007/s10140-020-01818-w
|View full text |Cite
|
Sign up to set email alerts
|

Responding to coronavirus disease 2019: LA County hospital experience

Abstract: The coronavirus disease 2019 has rapidly spread across the world since first being identified in Wuhan, China, in late 2019. In order to prepare for the surge of patients and the corresponding increase in radiology exams, clear and detailed policies need to be implemented by hospitals and radiology departments. In this article, we highlight the experiences and policies at LAC+USC Medical Center, the largest single provider of healthcare in LA County. Our policies aim to reduce the risk of transmission, guide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…Similarly, previous studies have shown that imaging volume decreased elsewhere in the country as well, including at institutions in the state of New York and in Santa Clara County, California, all within a week of the observed decrease at our institution (11,14). It was during this time that the WHO declared the COVID-19 outbreak a pandemic; together with subsequent CDC and American College of Radiology recommendations, this led to changes in not only our hospital system policies, but all health care systems across the United States to delay nonessential imaging studies as part of the widespread effort to slow the rate of new infections (10,16,17,20). The change in our hospital's and referring providers imaging orders, decision to suspend screening programs and nonurgent elective procedures, and patients' decisions to delay imaging, resulted in a 58% drop in weekly volume, which is comparable to the 20% to 60% decrease reported at other institutions (9,11,20,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, previous studies have shown that imaging volume decreased elsewhere in the country as well, including at institutions in the state of New York and in Santa Clara County, California, all within a week of the observed decrease at our institution (11,14). It was during this time that the WHO declared the COVID-19 outbreak a pandemic; together with subsequent CDC and American College of Radiology recommendations, this led to changes in not only our hospital system policies, but all health care systems across the United States to delay nonessential imaging studies as part of the widespread effort to slow the rate of new infections (10,16,17,20). The change in our hospital's and referring providers imaging orders, decision to suspend screening programs and nonurgent elective procedures, and patients' decisions to delay imaging, resulted in a 58% drop in weekly volume, which is comparable to the 20% to 60% decrease reported at other institutions (9,11,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It was during this time that the WHO declared the COVID-19 outbreak a pandemic; together with subsequent CDC and American College of Radiology recommendations, this led to changes in not only our hospital system policies, but all health care systems across the United States to delay nonessential imaging studies as part of the widespread effort to slow the rate of new infections (10,16,17,20). The change in our hospital's and referring providers imaging orders, decision to suspend screening programs and nonurgent elective procedures, and patients' decisions to delay imaging, resulted in a 58% drop in weekly volume, which is comparable to the 20% to 60% decrease reported at other institutions (9,11,20,21). As daily new cases of COVID-19 began to decrease by April 17th, 2020, and as Massachusetts began easing restrictions in May, we observed a steady recovery of volume; by May 21st, the daily imaging volume recovered to 68% of pre-SOE daily volume averages-70% at the main hospital campus, and 66% at affiliated imaging centers (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, working remotely is recommended whenever feasible. [ 37 ] Furthermore, while reading, consider potential COVID-19-related findings (specifically at SPECT-CT or PET-CT procedures). Report such findings to the patient and the referring physicians immediately for proper decision.…”
Section: Keep Personnel Safementioning
confidence: 99%
“…In recent months, the US has, unfortunately, struggled with many of the same challenges as Italy in mounting a homogenous governmental response. Conflicting guidelines and regional resource availabilities forced many institutions to internally devise their own policies and screening protocols, resulting in a patchwork of inconsistent practices regarding appropriate use of diagnostic technologies around the country [ 15 , [93] , [94] , [95] , [96] , [97] , 103 ]. Due to concerns over specificity of findings and unclear effect on clinical outcomes, the American College of Radiology is currently recommending against the use of both chest X-ray and chest CT to screen for COVID-19 [ 95 ].…”
Section: Updates From the United Statesmentioning
confidence: 99%